2019
DOI: 10.1002/cncr.32048
|View full text |Cite
|
Sign up to set email alerts
|

Delays in radical cystectomy for muscle‐invasive bladder cancer

Abstract: Background Delays from the diagnosis of muscle‐invasive bladder cancer (MIBC) to radical cystectomy (RC) longer than 12 weeks result in higher mortality and shorter progression‐free survival. This study sought to identify factors associated with RC delays and to determine whether delays in care in the current treatment paradigm, which includes neoadjuvant chemotherapy (NAC), affect survival. Methods Subjects with American Joint Committee on Cancer stage II urothelial carcinoma of the bladder who underwent RC f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 34 publications
1
47
0
Order By: Relevance
“…This left 34 studies with unique populations for inclusion ( fig 1 , table 1 , table 2 ). 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 These studies included 1 272 681 patients, with a sample size ranging from 174 to 420 792 (appendix 3). Twenty eight studies were population or registry based, and six were institutional reports.…”
Section: Resultsmentioning
confidence: 99%
“…This left 34 studies with unique populations for inclusion ( fig 1 , table 1 , table 2 ). 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 These studies included 1 272 681 patients, with a sample size ranging from 174 to 420 792 (appendix 3). Twenty eight studies were population or registry based, and six were institutional reports.…”
Section: Resultsmentioning
confidence: 99%
“…In contrary, a repeat analysis of the SEER and Medicare claims database compared patients who received NAC to those who did not. In comparison with timely surgery (defined as surgery within 12 weeks from diagnosis), delays in RC increased overall mortality, regardless of the use of NAC (hazard ratio [HR] without NAC, 1.34; 95% confidence interval [CI], 1.03−1.76; HR after NAC, 1.63; 95% CI, 1.06−2.52) [25].…”
Section: Muscle Invasive Bladder Cancer (Mibc)mentioning
confidence: 99%
“…Prior studies have shown that patients who are older, are African American, or are insured by Medicaid/Medicare are less likely to be treated at high‐volume centers, and this suggests a role for additional resources and support for such at‐risk populations. In the current study, Chu et al similarly demonstrate that delays may be influenced by nonclinical and socioeconomic factors, and they correctly argue for the need for quality improvement and health policy innovations to improve the timeliness of care, health disparities, and oncologic outcomes. As we continue to treat patients with muscle‐invasive bladder cancer in an ever‐evolving health care system, we must remain focused on implementing sound policies that benefit patients on an individual and national level, minimize treatment delays, and do not leave out the most vulnerable members of society, who are already the most likely to be affected by untoward consequences of reform.…”
mentioning
confidence: 57%
“…Indeed, among patients proceeding to RC without NAC, Chu et al found that delays in RC were more likely among men, patients from poor or rural areas, and those who transferred care between TURBT and RC. Tomaszewski et al previously showed that transitions in care resulted in treatment delays for patients with bladder cancer.…”
mentioning
confidence: 99%